The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Eau Et Environnement
DOI: 10.4000/books.enseditions.871
|View full text |Cite
|
Sign up to set email alerts
|

Régionalisation des pluies annuelles dans l’Algérie nord-occidentale

Abstract: La pluviométrie présente un intérêt majeur comme signature au-delà de son apport pour la définition du climat. Sa régionalisation s'avère très utile dans de nombreuses applications où il est nécessaire de minimiser la variabilité spatiale du paramètre analysé : détermination des « stations étalons », contrôle et reconstitution de données manquantes (Champeaux et al.,1996).L'objectif d'une régionalisation (ou zonage) climatique est d'obtenir un découpage d'un territoire en zones homogènes, à l'intérieur desquel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Taïbi et al (2013) analyzed more than 100 rainfall series over northern Algeria and demonstrated a significant decrease of annual rainfall in northwestern Algeria since the 1970s and 1980s, while rainfall variability in the eastern region did not change. Other studies also showed a decrease in rainfall in northwest Algeria (Meddi and Hubert, 2003;Medjerab et Henia, 2005; Talia, 2007;Bekkoussa et al, 2008;Meddi et al, 2010;Taibi and Souag, 2011) and other regions of the Mediterranean basin such as Spain (de Luis et al, 2000;Sinoga et al, 2011), Italy (Longobardi et Villani, 2009;Caloiero et al, 2011), Greece (Xoplaki et al, 2000;Feidas et al, 2007) Morocco (Benassi, 2001;Singla et al, 2010) and Tunisia (Kingumbi et al, 2005). Several studies correlate rainfall variability in the Mediterranean basin with the influence of general atmospheric circulation (van Oldenborgh et al, 2000;Lloyd-Hughes and Saunders, 2002;Knippertz et al, 2003;Xoplaki et al, 2004;López and Frances, 2010;Brandimarte et al, 2011).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Taïbi et al (2013) analyzed more than 100 rainfall series over northern Algeria and demonstrated a significant decrease of annual rainfall in northwestern Algeria since the 1970s and 1980s, while rainfall variability in the eastern region did not change. Other studies also showed a decrease in rainfall in northwest Algeria (Meddi and Hubert, 2003;Medjerab et Henia, 2005; Talia, 2007;Bekkoussa et al, 2008;Meddi et al, 2010;Taibi and Souag, 2011) and other regions of the Mediterranean basin such as Spain (de Luis et al, 2000;Sinoga et al, 2011), Italy (Longobardi et Villani, 2009;Caloiero et al, 2011), Greece (Xoplaki et al, 2000;Feidas et al, 2007) Morocco (Benassi, 2001;Singla et al, 2010) and Tunisia (Kingumbi et al, 2005). Several studies correlate rainfall variability in the Mediterranean basin with the influence of general atmospheric circulation (van Oldenborgh et al, 2000;Lloyd-Hughes and Saunders, 2002;Knippertz et al, 2003;Xoplaki et al, 2004;López and Frances, 2010;Brandimarte et al, 2011).…”
Section: Discussionmentioning
confidence: 78%
“…Many studies have shown a significant decrease in the temporal variability of rainfall in northwest Algeria (Medjerab and Henia, 2005;Meddi and Talia, 2007;Meddi and Hubert, 2003;Bekkoussa et al, 2008;Meddi et al, 2010;Taibi and Souag, 2011). This decrease is mostly observed during winter and spring (Taibi et al, 2013).…”
Section: Study Area and Data Setmentioning
confidence: 99%
“…a), the average annual rainfall varies from 194 mm (Ras El Ma station, code number 4) to 874 mm (El Milia station code number 24) (Table 1). Spatially, rainfall is distributed in four areas[22]:(i) The central highlands, Sersou and Ras El Ma regions, though situated at high altitude, are sheltered compared to wet currents, where rainfall is less than 300 mm.…”
mentioning
confidence: 99%
“…All sites prospected are located in different bioclimatic zones: subhumid, semiarid, arid (medium and inferior arid) and Saharan. The classi cation of these bioclimates is made through 3 main criteria: average annual rainfall, average daily minimum temperature of coldest month and average daily maximum of coldest month (Le- Houérou et al 1977;Le-Houérou 1995;Benabadji and Bouazza 2000;Medjerab and Henia 2005;Bensenane et al 2013). Surveys were carried out at various sites from January to March during thirty growing season of desert tru es to collect ascomata samples and to note some ecological factors of these hypogeous fungi.…”
Section: Methodsmentioning
confidence: 99%